A SOJA TRANSFORMANDO CHAPADÃO DO SUL / The soyabean cultivation transforming Chapadão do Sul (MS) - Jonas Romão da Rocha; Vera Lúcia Salazar Pessôa (Sociedade & Natureza)
The goal of this study is to point out the influence of the soya bean in the development andmodernization of the agriculture in the city of Chapadão do Sul (in the state of Mato Grosso doSul – Brazil) since 1980. In order to get a better view of that process, it was necessary a briefreport on how such agricultural modernization took place in Brazil, showing its effects in thefarming performance, altering the country’s economy and the way of life of the rural populationdue to the use of new technology resulted from the industrial process. Whit that report it waspossible to portray the advance of agriculture in the west center region of Brazil as well as itsdevelopmente in the city of Chapadão do Sul